Integrin mediated regulation of apicobasal polarity, cell states and cancer progression - Pasquier, Nicolas (fi=Turun yliopisto|en=University of Turku|, 2024)
Integrins regulate cell adhesion, migration and architecture which play a role both in development of healthy tissues and disease. While integrins have been widely studied amongst models, the way their availability acts on polarity, spreading and cell capacitation is not fully understood. Here we investigate the role of integrins, and mainly integrin-β1, on polarity establishment as well as cell spreading in cancer models. We also decipher their action on cell states by studying their role in human induced pluripotent stem cells (hiPSCs) capacitation. This thesis reveals a newly described SorLA, HER2 and HER3-dependent Integrin-β1 recycling loop, allowing colon cancer cells to sense the matrix and orient their polarity accordingly. We also go deeper in cancer cell spreading on matrix, by identifying two matrix compositions (collagen + laminin and laminin + tenascin C) allowing osteosarcoma cancer cells and fibroblasts to spread in a stiffness- independent fashion through an increased amount of integrin-β1-positive molecular clutches. We also investigate the role of Integrin-β1 on the capacitation process of stem cells and show that inhibition of integrin-β1 maintains a naïve-like phenotype in hiPSCs. Taken together, these data highlight the importance of integrins, and mainly integrin-β1, in many cell processes amongst models, thus explaining its key role in cell adhesion, cancer cell architecture and cell state establishment.